1982
DOI: 10.3758/bf03332935
|View full text |Cite
|
Sign up to set email alerts
|

Brain lesions impairing visual and spatial reversal learning in rats: Components of the “general learning system” of the rodent brain

Abstract: The "general learning system" (GLS) is conceived as an ensemble of brain structures essential for normal acquisition of a wide variety of laboratory tasks. Based upon earlier lesion studies, it was reasoned that the components of the rodent's GLS could be identified by determining which lesion placements within the rat brain would lead to defective acquisition of a spatial discrimination habit and its reversal as well as a brightness discrimination habit and its reversal. Of the 11 cortical and subcortical (fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

1984
1984
1995
1995

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 61 publications
1
9
0
Order By: Relevance
“…The foregoing findings, which implicate the globus pallidus, substantia nigra, median raphe, and pontine reticular formation in the general learning process, are significant for a number of reasons. First, it should be recognized that a generalized learning impairment induced by specific brain lesions is not a common occurrence: Rats with discrete lesions to the cerebral cortex, limbic forebrain, caudoputamen, nucleus accumbens, thalamus, medial hypothalamus, dorsal midbrain, lateral pontomesencephalic area, or cerebellar cortex have not been found to exhibit a generalized learning impairment (Thompson, 1982a(Thompson, , 1982b; current study). Such a localized effect suggests that the neuronal elements intrinsic to (or extraneous fibers passing through) the regions of the globus pallidus, substantia nigra, median raphe, and pontine reticular formation are potentially more involved in the ability to learn diverse laboratory tasks than those associated with most other regions of the brain.…”
Section: The General Learning Systemmentioning
confidence: 66%
See 3 more Smart Citations
“…The foregoing findings, which implicate the globus pallidus, substantia nigra, median raphe, and pontine reticular formation in the general learning process, are significant for a number of reasons. First, it should be recognized that a generalized learning impairment induced by specific brain lesions is not a common occurrence: Rats with discrete lesions to the cerebral cortex, limbic forebrain, caudoputamen, nucleus accumbens, thalamus, medial hypothalamus, dorsal midbrain, lateral pontomesencephalic area, or cerebellar cortex have not been found to exhibit a generalized learning impairment (Thompson, 1982a(Thompson, , 1982b; current study). Such a localized effect suggests that the neuronal elements intrinsic to (or extraneous fibers passing through) the regions of the globus pallidus, substantia nigra, median raphe, and pontine reticular formation are potentially more involved in the ability to learn diverse laboratory tasks than those associated with most other regions of the brain.…”
Section: The General Learning Systemmentioning
confidence: 66%
“…The results of the current study add to this pattern to the extent that median raphe lesions were found to induce impairments in detour problem-solving behavior as striking as those induced by hippocampal lesions (Thompson et al, 1984a). However, a visual discrimination task appears to differentiate rats with large median raphe lesions from rats with large dorsal or ventral hippocampal lesions: The former exhibit dramatic deficits in acquisition (Thompson, 1982b) and retention (Thompson, 1978) of a white-black discrimination, whereas the latter do not exhibit these deficits (Thompson, 1978(Thompson, , 1982a(Thompson, , 1982b. Conceivably, damage to certain elements within the median raphe (serotonergic cells, nonserotonergic cells, or fibers in passage) may be responsible for the pattern of deficits similar to that associated with hippocampal lesions, whereas damage to other elements may be responsible for the visual discrimination impairments.…”
Section: General Findingsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although not conclusive, evidence exists which casts doubt on such a causal relationship. For example, the hippocampus of rodents has been implicated in both inhibitory (Douglas, 1967) and attentional (Oades, 1982) processes; yet young or adult rats with hippocampal lesions do not exhibit a generalized learning impairment (Douglas, 1967;Thompson, 1982a;Thompson & Yu, 1983). Other brain regions, to mention a few, which have been implicated in one or both of these processes include the frontal cortex (Stuss Thompson, 1978b), amygdala (Nagel & Kemble, 1976;Thompson, 1978b), and lateral lemniscal midbrain area (Sprague, Levitt, Robson, Liu, Stellar, & Chambers, 1963).…”
Section: Deficits In Response Inhibition and Attention 495mentioning
confidence: 99%